Strategies for the induction of anti-inflammatory mesenchymal stem cells and their application in the treatment of immune-related nephropathy - Zhou, Cheng; Bai, Xue-Yuan (Frontiers in Medicine, 2022)
Mesenchymal stem cells (MSCs) have potent immunomodulatory functions. Animal studies and clinical trials have demonstrated that MSCs can inhibit immune/inflammatory response in tissues and have good therapeutic effects on a variety of immune-related diseases. However, MSCs currently used for treatment are a mixed, undefined, and heterogeneous cell population, resulting in inconsistent clinical treatment effects. MSCs have dual proinflammatory/anti-inflammatory regulatory functions in different environments. In different microenvironments, the immunomodulatory function of MSCs has plasticity; therefore, MSCs can transform into proinflammatory MSC1 or anti-inflammatory MSC2 phenotypes. There is an urgent need to elucidate the molecular mechanism that induces the phenotypic transition of MSCs to proinflammatory or anti-inflammatory MSCs and to develop technical strategies that can induce the transformation of MSCs to the anti-inflammatory MSC2 phenotype to provide a theoretical basis for the future clinical use of MSCs in the treatment of immune-related nephropathy. In this paper, we summarize the relevant strategies and mechanisms for inducing the transformation of MSCs into the anti-inflammatory MSC2 phenotype and enhancing the immunosuppressive function of MSCs.